CHARACTER EDUCATIONAL VALUES IN NOVEL RANTAU SATU MUARA WORKS OF AHMAD FUADI: LITERATURE SOCIOLOGY REVIEW - Febriana, Noni; Thahar, Harris Effendi; Ermanto, Ermanto (English Department FBS UNP, 2014)
This research is motivated by problems in the world of education, that the values of character education get less attention because more directed to the mastery of academic or cognitive aspects. While the actual nonakademik aspect becomes the main foundation in character education less attention, so less embedded in learners. Therefore, this study aims to instill the values of character education contained in the novel Rantau Satu Muara by Ahmad Fuadi. This novel is chosen because it is closely related to the values of character education. The type of this research is qualitative with descriptive analysis method. This research also uses the approach of literary sociology. The data collection is done by the researchers themselves. The researcher recorded and analyzed the data during the research to collect the data taken in the novel text then the researchers themselves processed and analyzed the data in detail. The results of this study are the values of character education in the novel Rantau Satu Muara by Ahmad Fuadi which contains the values of character education, as follows. (1) Educational values of religious characters with indicators of sincerity, diligent worship / prayer, prayer, thanksgiving, and put your trust in. (2) The values of hard work character education with indicators of earnest, unyielding, aspiring and creative. (3) The values of education of the love character of the homeland with nationalist indicators and respect for diversity. (4) Educational values of the character communicative / friendly with indicators of cooperation, social care, love out, affection, kindness and respect the achievements of others. (5) The educational values of the characters love to read with the indicators of love science and diligent reading. (6) Values of character education responsibilities with independent indicators.